2016
DOI: 10.1177/0300985816655852
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Renal Lesions in Chickens After Experimental Infection With 9a5b Newcastle Disease Virus Mutant Isolate

Abstract: In this study, we investigated the pathogenesis of Newcastle disease virus (NDV) in the chicken kidney. Twenty-six 32-day-old specific pathogen-free chickens were intranasally inoculated with the 9a5b NDV mutant isolate. Kidney tissue samples, collected at 6 and 12 hours postinoculation (hpi) and 1, 2, 3, 5, and 10 days postinoculation (dpi), were analyzed by histopathology, immunohistochemistry (IHC), reverse transcription polymerase chain reaction (RT-PCR), and virus titration. Histopathologically, tubuloint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…In our study, viral antigen was expressed in several areas of infected kidneys, similar results obtained by El-Bahrawy et al (2017) who stated that most immunostaining for NDV-NP was distributed in a multifocal pattern in the intact and vacuolated epithelium of proximal and distal tubules, in infiltrating macrophages, in some cells of reptilian-type glomeruli in the cortex, and in medullary cones mainly in the tubular epithelium and the infiltrating mononuclear cells. Moreover, Susta et al (2011) stated that several epithelial cells in the distal tubules of the kidneys had positive signal for ND.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, viral antigen was expressed in several areas of infected kidneys, similar results obtained by El-Bahrawy et al (2017) who stated that most immunostaining for NDV-NP was distributed in a multifocal pattern in the intact and vacuolated epithelium of proximal and distal tubules, in infiltrating macrophages, in some cells of reptilian-type glomeruli in the cortex, and in medullary cones mainly in the tubular epithelium and the infiltrating mononuclear cells. Moreover, Susta et al (2011) stated that several epithelial cells in the distal tubules of the kidneys had positive signal for ND.…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, Echols et al (2006) mentioned that blood uric acid levels are mildly affected by the birds' hydration status, but they reflect the functional capacity of the renal proximal tubules. Loss of renal function combined with water deprivation during the peak of clinical signs may enhance the effect (El-Bahrawy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 80 % of nitrogen excreted by birds is in the form of uric acid through tubular secretion (Okorie-Kanu et al, 2016). Renal lesions due to NDV have been determined in several avian species (El-Bahrawy, 2016). These results were confirmed by histopathological changes of kidney, which showing focal coagulative necrosis with replacement of necrotic tissue with mononuclear cells (Arrow) (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Many reports have demonstrated that the avian infectious bronchitis ( IB ) virus and Newcastle disease ( ND ) virus infect the kidneys of immature and mature chickens, causing pathological changes and disease ( Chen and Itakura, 1996 ; Cong et al, 2013; Bande et al, 2016 ; El-Bahrawy et al, 2017 ). Inoculation of chickens with Marek’s disease ( MD ) virus isolated from CVI988/Rispens-vaccinated chickens caused tumors, mainly in the spleen, liver, and kidney ( Cui et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%